Self-locomotion and spatial language and spatial cognition: insights from typical and atypical development - Oudgenoeg-Paz, Ora; Rivière, James (Frontiers in Psychology, 2014)
Various studies have shown that occurrence of locomotion in infancy is correlated with the development of spatial cognitive competencies. Recent evidence suggests that locomotor experience might also be important for the development of spatial language. Together these findings suggest that locomotor experience might play a crucial role in the development of linguistic-cognitive spatial skills. However, some studies indicate that, despite their total deprivation of locomotor experience, young children with spinal muscular atrophy (SMA) have the capacity to acquire and use rich spatial representations including good spatial language. Nonetheless, we have to be cautious about what the striking performances displayed by SMA children can reveal on the link between motor and spatial development, as the dynamics of brain development in atypically developing children are different from typically developing children.